Five Senses for Effective and Sustainable Corporate Social Responsibility Strategy - Al Mubarak, Muneer Mohamed Saeed (International Journal of Economics and Financial Issues, 2019)
This study presents the five senses (sight, hearing, taste, touch and smell) concept that enhances the corporate social responsivity (CSR) strategy. It sheds light on the true CSR senses which are required by firms for better performance and sustainable development. The main approach for collecting information for discussion was the literature review focusing on topics such as CSR strategy, CSR activities, sustainability and sensemaking. A gap was found between what firms do and what are expected to deliver to the society in terms of CSR activities and requirements. Little was found on sensemaking and very little was found on CSR five senses while searching the literature. When these five CSR senses are incorporated in firms’ strategy and activities, a better performance is expected to achieve. When firms work effectively to meet different stakeholders’ needs and wants internally and externally, a better satisfaction level can be achieved, hence sustainable development is likely to be secured. These five CSR senses have not been sufficiently considered in the research literature. This study contributes to the CSR knowledge and practice in many venues by bridging the CSR gap which might exist in strategy and practice. Therefore, researchers and practitioners are expected to benefit from this study that can result in better CSR control and sustainable development. Keywords: Five senses, Corporate social responsibility, Sustainability, Sensemaking, Stakeholders JEL Classifications: M140 DOI: https://doi.org/10.32479/ijefi.8990